Sistem Pakar Diagnosa Tingkat Depresi pada Mahasiswa Menggunakan Metode Fuzzy Tsukamoto Berbasis Web - Yuliana, Yuliana; Arhami, Muhammad; Hendrawaty, Hendrawaty (Jurnal Teknologi Rekayasa Informasi dan Komputer, 2023)
Depression is a mental disorder in the nature of feelings or moods characterized by symptoms of moodiness,lethargy, no passion for life, feeling useless, deep disappointment, hopelessness, thoughts of death and suicidal ideation. Ifyou experience feelings of sadness and hopelessness, it is normal for someone to feel, but if the condition is experienced for months for no apparent reason. So it can be concluded that one of the signs of depression that appears. In general, depression can be divided into three levels, namely mild depression, moderate depression and severe depression. Depression can happen to everyone, including in the world of education such as students. The level of depression in college students has increased compared to the age of children and adults. People with depression tend not to pay attention to their diet and physical activity. In general, students do not know how much depression is experienced and students also do not have knowledge about how to prevent depression, so we need a system that can diagnose depression levels. Based on these problems, an expert system was designed to diagnose the level of depression in students using the Web-based Fuzzy Tsukamoto method. This system is designed for Lhokseumawe State Polytechnic students. This system uses the Fuzzy Tsukamoto method which is used to diagnose depression levels in students. The results of the percentage of test dataobtained in this system are 76%.Keywords — Expert System, Diagnosis, Depression, Fuzzy Tsukamoto, Web